Modeling the quality of sewage during the leaking of stormwater surface runoff to the sanitary sewer system using SWMM: a case study - Maryam Hassan Mohammed; Haider M. Zwain; Waqed Hammed Hassan (Aqua, 2022)
This paper describes the application of the storm water management model (SWMM) for predicting the sewage quality in the sanitary sewer system of the study area resulting from the leaking of stormwater surface runoff to the system during rainfall events at different return periods. The concentrations of major pollutants were assessed in the sanitary sewer system at different rainfall intensities. Then, a solution to mitigate the problem was proposed using low impact development (LID) technology. The results of sensitivity analysis indicated that maximum build-up possible was the most sensitive parameter for model calibration. The model was calibrated using actual rainfall events, and statistical validation coefficients of R (0.81–0.82) and NMSE (0.0173–0.022) proved that the model is valid. The sewage quality assessment results showed that pollutants concentration increased to its maximum level at 20 min and gradually decreased to a slightly constant minimum value after 2 h. The proposed solution of LID reduced the pollutants concentrations by 82–88, 75–77, 52–55, and 7–10% for all pollutants at return periods of 2, 5, 10, and 25 years, respectively. To conclude, SWMM simulation successfully predicted the concentration of the pollutants, and leaking of stormwater surface runoff has changed the sewage quality. HIGHLIGHTS Storm water management model (SWMM) simulated the leaking of stormwater surface runoff into the sanitary sewer system.; Sewage quality in the sewer system highly influenced by stormwater surface runoff leaking.; Low impact development (LID) strategies have been applied to mitigate stormwater surface runoff leaking.; An important information on stormwater and sewage management for decision makers, sanitary experts, and stockholders has been provided.;